PENGARUH LEVERAGE TERHADAP MANAJEMEN LABA DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI (Pada Sektor Industri Dasar dan Kimia Yang Terdaftar di BEI Periode 2013-2017) - Muhsin N Bailusy; Fadli Ali Taslim (Jurnal Manajemen Sinergi, 2019)
Financial statements are the most important things that investors pay attention to. Sometimes companies practice earnings management to attract investors. Earnings management is a manager's actions to see accounting policies or actions that affect earnings in order to achieve the objectives in the income statement. This study aims to determine (1) the effect of leverage on earnings management. (2) Effect of Leverage on earnings management with the Independent Board of Commissioners as a moderating variable. The research sample of 19 companies. The data collection technique is done by the documentation method, which is collecting data in the form of literature books, journals, and the company's annual financial statements. The data needed in this study is secondary data derived from the financial statements of manufacturing companies in the basic and chemical industry sectors listed on the IDX period 2013-2017. The financial statements were downloaded from the site www.idx.co.id. The analysis technique used is quantitative. The results showed that leverage had a significant negative effect on earnings management and Implementation of good corporate governance which is proxied by an independent board of commissioners is able to moderate the effect of leverage on earnings management